Species of questing ixodid ticks on the vegetation of sable antelope (Hippotragus niger) enclosures and a surrounding multi-herbivore enclosure - Horak, Ivan Gerard (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2014.